Clusters of health behaviours in Queensland adults are associated with different socio-demographic characteristics. (13th March 2018) - Hobbs, M; Duncan, M J; Collins, P; Mckenna, J; Schoeppe, S; Rebar, A L; Alley, S; Short, C; Vandelanotte, C
Abstract: Background: The co-occurrence of unhealthy lifestyles, calls for interventions that target multiple health behaviours. This study investigates the clustering of health behaviours and examines demographic differences between each cluster. Methods: In total, 934 adults from Queensland, Australia completed a cross-sectional survey assessing multiple health behaviours. A two-step hierarchical cluster analysis using multiple iterations identified the optimal number of clusters and the subset of distinguishing health behaviour variables. Univariate analyses of variance and chi-squared tests assessed difference in health behaviours by socio-demographic factors and clusters. Results: Three clusters were identified: the 'lower risk' cluster ( n = 436) reported the healthiest profile and met all public health guidelines. The 'elevated risk' cluster ( n = 105) reported a range of unhealthy behaviours such as excessive alcohol consumption, sitting time, fast-food consumption, smoking, inactivity and a lack of fruit and vegetables. The 'moderate risk behaviour' cluster ( n = 393) demonstrated some unhealthy behaviours with low physical activity levels and poor dietary outcomes. The 'elevated risk' cluster were significantly younger and more socio-economically disadvantaged than both the 'lower and moderate risk' clusters. Discussion: Younger people who live in more deprived areas were largely within the 'elevated risk' cluster and represent an important population for MHBC interventions given their wide range of unhealthy behaviours.